Determinants of Firm Value: Solvency, Firm Growth, and Dividend Policy Impact on Food and Beverage Companies (Proceeding of the International Conference on Management, Entrepreneurship, and Business, 2025)
In 2024, Indonesia’s food and beverage industry recorded IDR 110.57 trillion in investment and achieved GDP growth above the national average, highlighting its rapid development and importance for the economy. However, this growth does not automatically increase firm value, as internal factors such as solvency, firm growth, and dividend policy may play a crucial role. This study investigates how those factors affect firm value in food and beverage companies listed on IDX during 2021–2024. The research population comprises 84 companies, with purposive sampling resulting in 47 observations from 13 firms over four years. Data were collected from annual reports and analyzed applying multiple linear regression with SPSS 26. The results show that solvency and dividend policy don’t significantly affect firm value, while firm growth has a significant positive impact. Simultaneously, all three variables positively influence firm value with an adjusted R² of 11.8%. The paper enriches the academic discussion by validating the applicability of signaling theory in showing that firm growth acts as a stronger signal compared to solvency or dividend policy in the food and beverage industry, offering useful implications for investors and managers.